Better living with dementia : implications for individuals, families, communities, and societies - Gitlin, Laura N., 1952-; Hodgson, Nancy A. (Academic Press is an imprint of Elsevier, 2018)
This book highlights evidence-based best practices for improving the lives of patients with dementia. It presents the local and global challenges of these patients, also coupling foundational knowledge with specific strategies to overcome these challenges. It also examines the trajectory of the disease, offers stage-appropriate practices and strategies to improve quality of life, provides theoretical and practical frameworks that inform on ways to support and care for individuals living with dementia, includes evidence-based recommendations for research, and details global examples of care approaches that work. --